Root Anatomical Imaging and Phenotyping in Maize - Sidhu, Jagdeep Singh; Schneider, Hannah M (Cold Spring Harbor protocols, 2024)
Root anatomy plays a crucial role in regulating essential processes such as the absorption and movement of water and nutrients in plants. Root anatomy also impacts the energy costs of building and sustaining root tissues, tissue mechanics, and interactions with other organisms. Although several studies in maize have confirmed the functional utility of numerous root anatomical traits, such as that of cortical cell size and number for stress adaptation, there have been significant obstacles in measuring and analyzing root anatomical characteristics. This has resulted in gaps in our understanding of the genetic control and range of phenotypic variations among different cultivars, and how this diversity relates to overall fitness. Here, we review root anatomical phenotypes in maize and their function in stress adaptation, and briefly discuss phenotyping methods available for root anatomy. We further introduce a simple and accessible phenotyping approach that enables a comprehensive investigation of maize root anatomy. Detailed characterization of root traits and the implementation of robust methods for root anatomical phenotyping could have wide-ranging benefits across various areas of plant science, from fundamental research to enhancing crop breeding efforts.